2016
DOI: 10.1108/jibr-12-2015-0125
|View full text |Cite
|
Sign up to set email alerts
|

Relevance and evolution of adaptive markets hypothesis: a review

Abstract: Purpose The purpose of this paper is to discuss the relevance and evolution of adaptive markets hypothesis (AMH) that has gained traction in the recent years, as it provides a dynamic perspective to the concept of informational efficiency. Design/methodology/approach This paper discusses several issues related to the concept of informationally efficient markets that have indicated efficient market hypothesis to be an incomplete portrayal of stock market behavior. Findings The authors find that a strict and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…While on the other hand, EURO STOXX 50 results indicated that during bull periods there is considerably higher predictability, while during down periods, periods where the average return is negative, there is considerably lower predictability. The reader can refer to Dhankar and Shankar (2016) for a detailed literature review.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While on the other hand, EURO STOXX 50 results indicated that during bull periods there is considerably higher predictability, while during down periods, periods where the average return is negative, there is considerably lower predictability. The reader can refer to Dhankar and Shankar (2016) for a detailed literature review.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The adaptive market hypothesis (AMH) was proposed to show the predictability and operability of the stock market and its profit [18][19][20]. The AMH also gives us a more realistic perspective compared with the EMH.…”
Section: Adaptive Market Hypothesis and Imperfection Of Efficient-market Hypothesismentioning
confidence: 99%
“…According to Dhankar and Shankar (2016), there are several practical implications of AMH, namely: there is a dynamic risk-reward relationship that depends on the preferences of market participants; market efficiency is not a stable state; arbitrage opportunities exist from time to time and decrease as investors exploit them, and the non-periodic cyclical profitability of investment strategies suggests that a given strategy would perform well in one environment and perform poorly in another.…”
Section: Introductionmentioning
confidence: 99%